1987
DOI: 10.1128/aac.31.5.794
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative neutralization assay of fungicidal activity of disinfectants

Abstract: A quantitative assay using a neutralization medium was

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 14 publications
3
6
0
Order By: Relevance
“…17 Experimentally contaminated dry surfaces (Petri dishes) were partly decontaminated by lengthy heating in an oven, but not by MW irradiation. We confirmed that 70% ethanol is highly effective for decontaminating dry surfaces [18][19][20][21] and also found that washing with soap and water before ethanol treatment has no added benefit.…”
Section: Naturally and Experimentally Contaminated Foodssupporting
confidence: 68%
See 1 more Smart Citation
“…17 Experimentally contaminated dry surfaces (Petri dishes) were partly decontaminated by lengthy heating in an oven, but not by MW irradiation. We confirmed that 70% ethanol is highly effective for decontaminating dry surfaces [18][19][20][21] and also found that washing with soap and water before ethanol treatment has no added benefit.…”
Section: Naturally and Experimentally Contaminated Foodssupporting
confidence: 68%
“…22 Our findings can probably be extrapolated to other potentially pathogenic yeasts and molds, because A fumigatus spores are highly resistant to physical and chemical disinfectants. [18][19][20][21]23 Few data are available on nonAspergillus molds. Fusarium species are sensitive to alcoholic solution 24 and to high water temperature, 25 and MW heating to the boiling point is a rapid and convenient method for eradicating Candida albicans from milk.…”
Section: Naturally and Experimentally Contaminated Foodsmentioning
confidence: 99%
“…Lalitha and Rao [16], in a fourteen-day study, added Tween 80 to the facial cream to neutralize and verify the effectiveness of different preservatives that comprised methyl-and propylparabens. Likewise, Terleckyj and Axler [17] mixed the biocide with the neutralizer before addition of the challenge organisms to determine the neutralizing capacity of the neutralizer.…”
Section: Introductionmentioning
confidence: 99%
“…The CEN has established several EN standards in order to standardize the methods applied for testing antifungal activity of antiseptic and disinfectant agents. [16,22,23].…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of different microorganisms, often resistant to high concentrations of antibiotics and chemotherapeutics, especially among hospitalized patients, their presence on the surfaces of medical devices, hard surfaces, linen and in health care facilities, necessitates improved antisepsis and disinfection procedures using effective antimicrobial preparations [16,22]. The CEN has established several EN standards in order to standardize the methods applied for testing antifungal activity of antiseptic and disinfectant agents.…”
Section: Discussionmentioning
confidence: 99%